Methods of designing terminal facilities at the airport "Boryspil" considering external shock dynamic effects - Гирич, В.Ю. (Proceedings of National Aviation University, 2007)
General procedure of assassination risk estimation is developed. Fast-acting collision of aircraft with building is modeled. The basic mechanisms of building destruction at impact-dynamic influences are described (falling, impact of aircraft). Recommendations, which can be used for building stability estimation at the aircraft impact, are developed. Recommendations for air terminal stability provision against progressing destruction are presented.